2022
DOI: 10.1108/febe-06-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and strategies for sustainable project performance in the post-Covid era in Nigeria: a thematic analysis approach

Abstract: PurposeCovid-19 pandemic have raised serious health concerns, work disruptions and job loss. Thus, Nigeria’s Covid-19 challenges can hinder project performance in the construction sector. By integrating the principle of sustainable construction, it can minimise the environmental and socio-economic impact of Covid-19. This research therefore aims at developing strategies to achieve sustainable project performance in the post-Covid era in Nigeria.Design/methodology/approachA qualitative research method was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Tunji-Olayeni et al (2020) identified common sustainable practices to include compliance with health and safety regulation, waste management, energy efficiency and material reuse. Additionally, around this time, Babalola (2020) (Okoye and Okolie, 2013;Babawale and Oyalowo, 2013;Aghimiena et al, 2019;Oke et al, 2021;Adekunye and Oke, 2022;Isang and Ebiloma, 2023) have explored different aspects of sustainability in construction projects. Abolore (2012) and Okoye and Okolie (2013) applied environmental and social perspective to SC by showing that imbibing environmental protection and safety culture through management commitment, safety training and education, and instituting regulatory framework promotes SC practice in Nigeria.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Tunji-Olayeni et al (2020) identified common sustainable practices to include compliance with health and safety regulation, waste management, energy efficiency and material reuse. Additionally, around this time, Babalola (2020) (Okoye and Okolie, 2013;Babawale and Oyalowo, 2013;Aghimiena et al, 2019;Oke et al, 2021;Adekunye and Oke, 2022;Isang and Ebiloma, 2023) have explored different aspects of sustainability in construction projects. Abolore (2012) and Okoye and Okolie (2013) applied environmental and social perspective to SC by showing that imbibing environmental protection and safety culture through management commitment, safety training and education, and instituting regulatory framework promotes SC practice in Nigeria.…”
Section: 3mentioning
confidence: 99%
“…More recently, during the corona-virus (COVID-19) pandemic, many research in Nigeria established that the construction workforce experienced project disruptions (Ogunnusi et al, 2020), adverse effects (Yusuf et al, 2021) and contractual disputes (Salami et al, 2021). In response, Isang and Ebiloma (2023) thematically showed that the holistic application of environmental, economic and social sustainability themes while incorporating managerial, contractual and governmental strategies can help in achieving sustainable project performance in the post-COVID era in Nigeria. Additional progression in the field shows a continuous need for the enforcement of SC and GB policy framework in the Nigerian construction industry.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Involving all stakeholders and establishing a deeper understanding of how different factors like the type of customer, company profile and operating sector interact with each other is key in post pandemic PM. Isang and Ebiloma (2023) have conducted qualitative research on post-pandemic PM performance in Nigeria and highlighted that a lot of uncertainty exists around management strategies, which creates productivity issues. These issues are evolving over time and key challenges remain, related to project delays, sector-wide project contract reviews and cash flow issues.…”
Section: Introductionmentioning
confidence: 99%
“…Growth in the construction industry has increased exponentially, but there are many challenges caused by the Covid-19 pandemic on operational and financial. Several factors which affected are rising material prices, the lack of labor and materials, and the delay in duration [2]. Meanwhile, Negash et al (2021) [3] explained that the large amount of construction and demolition waste (CDW), coupled with poor management, creates burdens for the environment, society, and economy.…”
Section: Introductionmentioning
confidence: 99%